Laboratory tests for antiphospholipid syndrome diagnosis in pregnant women (2022)
Antiphospholipid syndrome (APS) is an autoimmune disease characterized by the presence of autoantibodies against proteins bound to negatively charged phospholipids. Obstetric antiphospholipid syndrome (APS) is characterized as an acquired autoimmune disorder associated with different obstetric complications, defined as a state of hypercoagulability, which causes a wide range of complications associated with placental insufficiency including recurrent gestational loss, fetal death, preeclampsia, preterm delivery, among others. Its diagnosis is based on the Sidney criteria which include adverse obstetric history such as: (i) three consecutive miscarriages and spontaneous abortions prior to 10 weeks gestation (ii) fetal loss on one or more occasions at 10 weeks gestation and (iii) fetal death or preterm delivery due to eclampsia or severe preeclampsia or placental insufficiency prior to 34 weeks gestation, and laboratory findings such as (i) two positive tests for lupus anticoagulant (LA) at least 12 weeks apart (ii) two positive results for acL IgG or IgM at least 12 weeks apart and (iii) two positive results for 2GPI IgG or IgM at least 12 weeks apart. The laboratory tests give rise to an antibody profile related to the risk of complications; thus establishing as a high-risk profile, the presence of AL accompanied or not by high titers for acL or aβ2GPI. On the other hand, it is important to perform a differential diagnosis with other thrombotic microangiopathies with implications in pregnancy and to rule out the presence of different entities that may course with production of antiphospholipid antibodies. Based on these aspects and the severity of the syndrome under study, articles are required to determine the importance of the laboratory tests used for the diagnosis of antiphospholipid syndrome in pregnant women.